Pendidikan Agama Islam dalam Konteks Globalisasi: Strategi untuk Membangun Pemahaman Keberagamaan yang Moderat - Nur Azizah (Journal on Education, 2024)
Islamic Religious Education (PAI) that support the development of a moderate religious understanding among students in the era of globalization. Globalization, which introduces foreign cultural values such as individualism and materialism, influences students’ religious perceptions, presenting challenges in maintaining their religious identity. Using a qualitative method involving in-depth interviews, participant observation, and document analysis of curriculum and teaching modules, this research finds that most teachers have attempted to apply discussion methods, case studies, and social simulations to instill values of moderation in PAI. The analysis reveals that although moderate values are beginning to be implemented, the PAI curriculum still predominantly emphasizes theoretical aspects, with limited scope for practical application of tolerance, inclusivity, and diversity in students’ social contexts. Meanwhile, discussion-based learning activities have proven effective in enhancing student engagement, encouraging critical thinking, and fostering openness to differences. This study recommends curriculum adjustments and teaching materials to make PAI learning more contextual and relevant, equipping students with a moderate religious perspective responsive to multicultural challenges in a globalized world